Regulasi Pengawasan Impor Pangan Segar di Indonesia dan Kesenjangannya dengan Kriteria Pengawasan Impor Pangan ASEAN - Fujio Lamtarida Panggabean; Dedi Fardiaz; Eko Hari Purnomo (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
Role of food import control in food trading is essential to protect consumer health and facilitate fair trade. Based on provision of ASEAN Trade in Goods Agreement (ATIGA), all country members of ASEAN including Indonesia is required to harmonize its national regulations, including food import control regulations with international regulations. This study was aimed to assess gap between fresh food import control regulations in Indonesia and ASEAN food import control criteria, assessing the implementation of Fresh Food Plant Origin (FFPO) import controls as case study, and developing recommendations. The results showed gap beetween fresh food import control regulations in Indonesia and ASEAN food import control criteria. Gaps identified were risk-based sampling plan, respond to emergency situations and decision making for non-conforming product by action: destroy by inspector; order to recondition, process, or designate as non-food use. Case study showed the implementation of FFPO import control need improvement. Amandement of regulation, upgrading the capacity of existing laboratories and personnel competency are needed for strengthening fresh food import control regula-tion in Indonesia.